2006
DOI: 10.1111/j.1467-9515.2006.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Pension Mix: Consequences for Dutch and Danish Women

Abstract: All European countries are aiming to reform their pension systems in line with two conceptual ideas: firstly, that systems should combine public, occupational and private pensions; secondly, that entitlements should be individualized. The Dutch and the Danish pension systems already consist of these three different pensions with relatively individualized entitlements and in a way form an ideal type of pension system. However, these systems are far from ideal since they are deeply gender biased. The positive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Furthermore, the specific character of the Dutch pension system might limit the generalizability of the findings to other countries (see for discussions on gender and pension systems Frericks et al 2006;Ginn et al 2001;Jefferson 2009). Third, the marital and work history variables were based on rather broad retrospective questions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the specific character of the Dutch pension system might limit the generalizability of the findings to other countries (see for discussions on gender and pension systems Frericks et al 2006;Ginn et al 2001;Jefferson 2009). Third, the marital and work history variables were based on rather broad retrospective questions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the specific character of the Dutch pension system might limit the generalizability of the findings to other countries (see for discussions on gender and pension systems Frericks et al 2006;Ginn et al 2001;Jefferson 2009). Second, the marital and work history variables were based on rather broad retrospective questions.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study of Denmark and the Netherlands, Frericks, Maier and de Graaf (2006) conclude that relatively better childcare facilities in Denmark contribute to observed benefits for women's access to pension coverage. In Denmark, childcare facilities are guaranteed for children from the age of 1 year, while thirty-two weeks of mandated parental leave is available and may be extended by agreement with an employer.…”
Section: Access To Childcarementioning
confidence: 93%
“…Parental leave entitles the person to up to thirty-two weeks of unemployment benefits, and women usually take leave because it represents a lower loss of earnings than is the case for many men. Thus, Frericks, Maier, and Graaf (2006) argue that while Denmark's childcare facilities compare favorably with the Netherlands, the costs of having children remain gender-biased, with women more likely to experience both low earnings and broken patterns of labor-market participation. The authors have also identified lower access to childcare facilities in the Netherlands as a crucial issue for Dutch mothers' capacity to successfully accumulate occupational pension entitlements (Frericks, Maier, and de Graaf 2006).…”
Section: Access To Childcarementioning
confidence: 96%
See 1 more Smart Citation